Agriculture MSMEs Sustainability Farmers Exchange Rates in Indonesia During the Covid-19 Pandemic and Farmer Empowerment Solutions - Supriatna, Jajang; Djumarno, Djumarno; Badawy Saluy, Ahmad; Kurniawan, Deden (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
In